Low socioeconomic status relates to asthma and wheeze, especially in women - Schyllert, Christian; Lindberg, Anne; Hedman, Linnea; Stridsman, Caroline; Andersson, Martin; Ilmarinen, Pinja; Piirilä, Päivi; Krokstad, Steinar; Lundbäck, Bo; Rönmark, Eva; Backman, Helena (ERJ Open Research, 2020)
Low socioeconomic status (SES) has been associated with asthma and wheezing. Occupational group, educational level and income are commonly used indicators for SES, but no single indicator can illustrate the entire complexity of SES. The aim was to investigate how different indicators of SES associate with current asthma, allergic and nonallergic, and asthmatic wheeze. In 2016, a random sample of the population aged 20-79 years in Northern Sweden were invited to a postal questionnaire survey, with 58% participating (n=6854). The survey data were linked to the national Integrated Database for Labour Market Research by Statistics Sweden for the previous calendar year, 2015. Included SES indicators were occupation, educational level and income. Manual workers had increased risk for asthmatic wheeze, and manual workers in service for current asthma, especially allergic asthma. Primary school education associated with nonallergic asthma, whereas it tended to be inversely associated with allergic asthma. Low income was associated with asthmatic wheeze. Overall, the findings were more prominent among women, and interaction analyses between sex and income revealed that women, but not men, with low income had an increased risk both for asthmatic wheeze and current asthma, especially allergic asthma. To summarise, the different indicators of socioeconomic status illustrated various aspects of associations between low SES and asthma and wheeze, and the most prominent associations were found among women. Peer reviewed